DETECTION OF AUTOREACTIVE CLASS M ANTIBODIES IN PATIENTS WITH RESPIRATORY VIRAL INFECTIONS - V. Z. Krivitskaya; M. V. Sverlova; V. F. Sukhovetskaya; N. I. Lvov; I. A. Vassilieva; A. A. Sominina (Медицинская иммунология, 2014)
Abstract. The aim of this study was to detect some features of autoreactive IgM production that interact with IgGs and normal human cellular antigens in blood sera of patients with acute respiratory viral infections caused by various factors, dependent on their age and clinical features of disease. The antibody concentrations were determined by immunoenzyme technique in paired serum samples from 750 patients and single specimens from 97 healthy persons. The results of analysis have shown that the studied types of autoreactive IgM represent a normal component of humoral immunity, since they are detectable in sufficient number of normal sera from healthy persons over 3 years old. In acute respiratory viral infections of different etiology, the rates of appropriate seroconversions comprised 0 to 16% for age cohort of < 3 years old. Incidence of seroconversions reached 37% among older children and adult patients with respiratory syncitial virus (RSV), or adenoviral infection, thus being 1.7 to 5.1-fold higher than in patients with influenza A, or B, or parainfluenza. In cases of clinical complications of RSV or parainfluenza infections (i.e., respiratory tract obstruction, or pneumonia), the rates of seroconversions to autoreactive IgMs was 1.4 to1.8-fold higher than among the patients with uncomplicated clinical course of these infections. (Med. Immunol., 2008, vol. 10, N 2-3, pp 229-238).